The Discursive Contradiction between Government Legitimacy and Labor Resistance: An Analysis of Fairclough's Critical Discourse on Two Perspectives of National Apprenticeship News in Kompas.com - Desyfa Cahya Aina; Sabrina Al Izzati; Siska Rakhmawati (Jurnal Sastra Indonesia, 2026)
This study aims to uncover the ideological dynamics and power relations in Kompas.com news about the National Apprenticeship Program using the Norman Fairclough model of Critical Discourse Analysis (CDA). The focus of the study is directed at two news texts that display the contradiction of representation between the legitimacy of the government and the resistance of labor unions, namely "Deputy Minister of Labor Calls Internship Program a Golden Bridge to the World of Work" (November 4, 2025) and "Trade Union Regarding the Ministry of Labor's Internship Program: Insulting Undergraduate Graduates" (October 14, 2025). The research method of this study is qualitative, with three stages of Fairclough's analysis: textual dimensions, discourse practices, and social practices. The results show that the government uses the language of development and modernization to legitimize apprenticeship policies through euphemistic strategies and progressive metaphors. At the same time, trade unions display resistant discourses that emphasize structural inequality and the degradation of workers' dignity. This contradiction of meaning confirms that the media has become an arena of hegemony that articulates and negotiates power. Through this study, critical discourse analysis can be seen as an important context in identifying the hidden ideologies behind news construction and fostering people's critical literacy of the media's language.